The Profits of Power: Land Rights and Agricultural Investment in Ghana - Goldstein, Markus (2012)
We examine the impact of ambiguous and contested land rights on investment and productivity in agriculture in Akwapim, Ghana. We show that individuals who hold powerful positions in a local political hierarchy have more secure tenure rights and that as a consequence they invest more in land fertility and have substantially higher output. The intensity of investments on different plots cultivated by a given individual corresponds to that individual's security of tenure over those specific plots and, in turn, to the individual's position in the political hierarchy relevant to those specific plots.